EMBR-03. PINEOBLASTOMA: A POOLED OUTCOME STUDY OF NORTH AMERICAN AND AUSTRALIAN THERAPEUTIC DATA. (1st June 2021) - Hansford, Jordan; Huang, Jie; Dodgshun, Andrew; Li, Bryan; Hwang, Eugene; Leary, Sarah; Gajjar, Amar; Von Hoff, Katja; Endersby, Raelene; Wells, Olivia; Wray, Alison; Kotecha, Rishi; et al.
Abstract: Background: Pineoblastoma (PB) is a rare embryonal brain tumour most often diagnosed in young children. To date, no clinical trials have been conducted specific to pediatric PB. Collaborative studies performed over the past 30 years have included PB in studies accruing for other embryonal tumours, primarily medulloblastoma (MB), but also including the entity formerly known as CNS-PNET and atypical teratoid rhabdoid tumors. Each of these studies have included only a small number of children with PB, making clinical features difficult to interpret and determinants of outcome difficult to ascertain. Patients and Methods: Published centrally reviewed series with sufficient treatment and outcome data from North American and Australian cases were pooled. To investigate associations between variables, Fisher's exact and Wilcoxon-Mann-Whitney tests, and Spearman correlations were used as appropriate. Kaplan-Meier plots, log-rank tests, and Cox proportional hazards models were used in survival analysis. Results: We describe a 30-year review of the reported clinical features of PB and a pooled centrally reviewed, cohort analysis of cases (n=178) from the Children's Oncology Group (COG) (n=82) groups and several published, centrally reviewed institutional series (n=96). We find young children <3 years of age have a dramatically poorer outlook compared to older children (5-year OS 16.2% +/- 5.3% vs 67.3% +/- 5%) confirming new and novel approaches are needed in future clinical trials for this at risk group. Interestingly, male gender was predictive of worse outcome possibly suggestive of gender specific subgroup risks that needs validation in future studies. Assessment of radiation therapy is not possible as the vast majority of children under age three did not receive any form of radiation therapy. Conclusion: Given the relative scarcity of this tumor and the emerging data on subgroups of pineoblastoma, prospective, collaborative international studies will be vital to improving the long-term survival of these patients.